Pulmonary Langerhans cell histiocytosis presenting as skin lesion in a young child exposed to chronic passive smoking: A case report - Jondhale, Sunil; Tiwari, Kavita; Jain, Rolly; Gupta, Rakesh Kumar; Shah, Seema; Goel, Anil Kumar (Indian Journal of Child Health, 2020)
Pulmonary Langerhans cell histiocytosis (PLCH) is a rare disease in childhood. We report a case of a 3-year-old boy who was exposed to chronic passive smoking in family presented with PLCH with isolated skin involvement. The boy presented with a history of recurrent respiratory tract infections requiring intensive care unit admissions for severe respiratory distress. The chest X-ray showed bilateral honeycombing of lungs, which was further confirmed by chest computed tomography showing diffused bilateral multiple cystic lesions with ground-glass haziness of lung parenchyma. Skin biopsy from suspected cutaneous lesions confirmed the diagnosis by positive S-100 and CD-1a. After initiating intensive chemotherapy, the patient showed significant improvement. Based on our experience, it can be suggested that knowledge of such condition with high clinical suspicion and simple skin biopsy can be a valuable modality in diagnosing PLCH in cases without putting the other internal organs at risk.